Untargeted Metabolomics Sheds Light on the Secondary Metabolism of Fungi Triggered by Choline-Based Ionic Liquids - Sequeira, Patrícia; Rothkegel, Maika; Domingos, Patrícia; Martins, Isabel; Leclercq, Céline C.; Renaut, Jenny; Goldman, Gustavo H.; Silva Pereira, Cristina (Frontiers in Microbiology, 2022)
Fungal secondary metabolites constitute a rich source of yet undiscovered bioactive compounds. Their production is often silent under standard laboratory conditions, but the production of some compounds can be triggered simply by altering the cultivation conditions. The usage of an organic salt – ionic liquid – as growth medium supplement can greatly impact the biosynthesis of secondary metabolites, leading to higher diversity of compounds accumulating extracellularly. This study examines if such supplements, specifically cholinium-based ionic liquids, can support the discovery of bioactive secondary metabolites across three model species: Neurospora crassa, Aspergillus nidulans, and Aspergillus fumigatus. Enriched organic extracts obtained from medium supernatant revealed high diversity in metabolites. The supplementation led apparently to increased levels of either 1-aminocyclopropane-1-carboxylate or α-aminoisobutyric acid. The extracts where bioactive against two major foodborne bacterial strains: Staphylococcus aureus and Escherichia coli. In particular, those retrieved from N. crassa cultures showed greater bactericidal potential compared to control extracts derived from non-supplemented cultures. An untargeted mass spectrometry analysis using the Global Natural Product Social Molecular Networking tool enabled to capture the chemical diversity driven by the ionic liquid stimuli. Diverse macrolides, among other compounds, were putatively associated with A. fumigatus; whereas an unexpected richness of cyclic (depsi)peptides with N. crassa. Further studies are required to understand if the identified peptides are the major players of the bioactivity of N. crassa extracts, and to decode their biosynthesis pathways as well.